1998
DOI: 10.1038/sj.bdj.4809796
|View full text |Cite
|
Sign up to set email alerts
|

A smoking cessation programme conducted through dental practices in the UK

Abstract: Motivated dentists with staff support and access to information on smoking counselling are able to contribute to tobacco control measures in the community. The success of this programme closely parallels those reported in general medical practice settings. In view of the very considerable attrition rates found at all levels of the programme in the present study and the uneven performance of the participating practices the quit rate reported here may not accurately reflect what could be achieved in an individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 0 publications
5
59
0
1
Order By: Relevance
“…9 The quit rates in this study compare favourably with previous studies carried out in the UK by dental personnel which showed quit rates of 11 to 18%. 10,11 Similar rates of 14-15% have been achieved by general medical practitioners. 12 The percentage of quitters tends to fall with time, indicating the difficulty in maintaining continuous abstinence.…”
Section: Discussionsupporting
confidence: 54%
“…9 The quit rates in this study compare favourably with previous studies carried out in the UK by dental personnel which showed quit rates of 11 to 18%. 10,11 Similar rates of 14-15% have been achieved by general medical practitioners. 12 The percentage of quitters tends to fall with time, indicating the difficulty in maintaining continuous abstinence.…”
Section: Discussionsupporting
confidence: 54%
“…30 Use of all primary healthcare providers in tobacco cessation activities should be facilitated by making pharmacological interventions for smokers easily available through dentists. A demonstration programme 31 in the South of England that allowed dentists to provide NRT in their practices (through prescriptions written by specialists) recorded a successful cessation rate of 11%, comparable to many GP-led studies. Dentists who wish to update their knowledge on the role they can play in helping patients quit tobacco should consult guidelines which are now available.…”
Section: Findings and Points Of Interestsupporting
confidence: 52%
“…35,36 These quit rates are much higher than population quit rates without health interventions. Furthermore, when multiplied by the number of attendees in dental practices, the public health impact of dentists' interventions could be enormous.…”
Section: Discussionmentioning
confidence: 99%